THE EVOLUTION OF PUBLIC-PRIVATE PARTNERSHIP IN THE FUEL AND ENERGY COMPLEX OF RUSSIA - O. Bolshakova; E. Israelyan (Вестник университета)
The article presents the results of studying the formation, the current state and prospects for the development of public-private partnership (PPP) in the fuel and energy sector in Russia. The authors consider the existing mechanisms of interaction between the public and private parties in the projects of the fuel and energy complex, including so-called quasi-PPP projects, i.e. relevant PPP on economic content. Such projects include production sharing agreements, special investment contracts, etc. Within the framework of the article, the authors highlight the main problems of the functioning of public-private partnership instruments and consider trends in the use of PPPs for the development of the fuel and energy complex in Russia